Students’ Dicipline in Mathematics Learning During Covid-19 Pandemic - Fina Hanifa Hidayati; Firsta Adilaturrahmah (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The low level of student discipline in learning mathematics can affect student learning outcomes. Students’ discipline in learning during a pandemic that takes place online is difficult to pay attention to. Therefore, it is necessary to conduct research to determine and observe the level of students’ discipline. This article aims to describe the level of discipline of junior high school students in participating in mathematics lessons during the Covid-19 pandemic. This is a qualitative descriptive case study research. The subjects in this study were 25 grade VII students of MTs Al-Amin Cikaso for the academic year 2020/2021. Data collection was done by interview, observation, and documentation. Technical data analysis includes data reduction, data presentation, and drawing conclusions. The results showed that: (1) the students had a high level of discipline in obeying school rules, (2) the students had a low level of discipline in participating in ongoing learning, (3) the students had a high level of discipline in carrying out the duties of the teacher, and (4) the students have a moderate level of discipline in carrying out learning at home. Keywords: learning discipline, learning mathematics, covid-19 pandemic.